Short Indian English stories an Analysis - KUNDAN KISHORE (International Journal of Multidisciplinary Research and Studies, 2021)
Two distinct styles may be identified within the realm of the Indian short tale written in English. The first type is that of fables, which often include either an instructive lesson or a universal truth about life. The characters do not represent actual people. However, the human focus is undeniably there in the moral implications that were discussed in the conclusion. The second type is the folk story, which has the only intention of entertaining its audience via the use of romance and adventure, but it is not sufficiently developed in a technical sense to produce an impression that is long-lasting. They encourage the use of one's imagination and provide a momentary reprieve from the harsh realities of the world. The short story in India has also acquired relevance as an efficient vehicle for the expression of cultural and social conditions, which has contributed to the country's rise in importance of this literary form. The Indian authors of short stories came to the conclusion that the form of the short story as it appeared in the ancient classics was particularly effective at communicating complex concepts in a manner that was easily understood. Therefore, the Indian author replaced the Gods and Heaven with Indians and India. He did this to make his point.